2022
DOI: 10.3389/fonc.2022.976810
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of prostate cancer and its associated factors among men 40 years of age and older in Mizan Aman town, Bench Sheko zone, Southern Nations, Nationalities, and Peoples’ Region, South West Ethiopia, 2019

Abstract: BackgroundProstate cancer is a common cause of morbidity and mortality among men aged 40 years and older. Evidence has shown that awareness of prostate cancer plays a greater role in the early detection of prostate cancer. However, there is a paucity of information regarding prostate cancer awareness levels in Ethiopia in general and in Mizan Aman town in particular.ObjectivesTo assess the awareness of prostate cancer and its associated factors among men aged 40 years and older in Mizan Aman, Bench Sheko zone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
0
0
Order By: Relevance
“…However, no significant relationship was found between income status and knowledge level in our study. Assefa et al [5] revealed in their studies, it has been revealed that the level of knowledge of individuals with a relatively higher income level will also be higher. However, in our study, no significant relationship was found between income status and level of knowledge.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, no significant relationship was found between income status and knowledge level in our study. Assefa et al [5] revealed in their studies, it has been revealed that the level of knowledge of individuals with a relatively higher income level will also be higher. However, in our study, no significant relationship was found between income status and level of knowledge.…”
Section: Discussionmentioning
confidence: 96%
“…Prostate cancer diagnosis, prevention, and treatment in recent decades have been heavily influenced by awareness and the intention to seek care for it. Men who were aware of the DRE/PSA test were more likely to have been screened compared to men who were not aware of it [5]. Therefore, it is important to measure the level of awareness among individuals regarding prostate cancer in the country.…”
Section: Introductionmentioning
confidence: 99%
“…The intersection of these barriers for male cancer patients creates a multifaceted landscape where acknowledging mental health needs feels at odds with societal norms. The fear of appearing weak or vulnerable due to societal expectations clashes with the innate necessity for support during their cancer journey (25). The amalgamation of denial, lack of awareness, and communication barriers encapsulates the challenges faced by male cancer patients when seeking essential mental health support.…”
Section: Barriers To Seeking Helpmentioning
confidence: 99%
“…Broadcast media coverage of health matters play major roles in shaping public opinion and views thereby influencing medical practice. Research conducted by Ashenafi, Gugsa and Gadisa in Ethiopia in 2019 [3] reveals that about 64 percent of the sample size have access to media messages on prostate cancer which shows that information regarding prostate cancer awareness level in Ethopia in General and in Mizan Aman town in Particular is high (Ashenafi et al 2019) [3] . Media advocacy on prostate cancer has increased compare to how it was in the 80s but there is the need for a collective effort towards increasing media advocacy on prostate cancer.…”
Section: Influence Of Broadcast Media Campaign Messages In Etsako Wes...mentioning
confidence: 99%